2002
DOI: 10.1063/1.1432450
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sub-diffraction-limit laser micro/nanoprocessing in a threshold material system

Abstract: We report on sub-diffraction-limit (SDL) micro/nanofabrication via two-photon-absorption (TPA) photopolymerization. SDL spatial resolution was found possible in a threshold system, where materials responded to light excitation with a pronounced threshold behavior. The diffraction limit in this case became just a measure of focal spot size, but did not put any actual restraint to voxel dimensions. Experimentally, lateral spatial resolution down to 120 nm was realized by using high numerical-aperture optics. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(134 citation statements)
references
References 14 publications
1
124
0
3
Order By: Relevance
“…Two-photon photopolymerization appears to overcome such limitations, and three-dimensional nanostructures (3D) can be fabricated. [286][287][288][289][290] Two recent examples illustrate application of conceptually different approaches in optical lithography based on two-photon absorption. It was demonstrated that initiating species can be generated by single-photon absorption at one wavelength while inhibiting species are generated by single-photon absorption at a second, independent wavelength.…”
Section: New and Emerging Applicationsmentioning
confidence: 99%
“…Two-photon photopolymerization appears to overcome such limitations, and three-dimensional nanostructures (3D) can be fabricated. [286][287][288][289][290] Two recent examples illustrate application of conceptually different approaches in optical lithography based on two-photon absorption. It was demonstrated that initiating species can be generated by single-photon absorption at one wavelength while inhibiting species are generated by single-photon absorption at a second, independent wavelength.…”
Section: New and Emerging Applicationsmentioning
confidence: 99%
“…MPP was first developed by Strickler and Webb, [62] and has now been used to create a range of high-resolution 3D free-form structures, including microchannels, [63][64][65] cantilevers, [66][67][68] microgears, [69,70] sub-micrometer oscillators, [71] hydrophobic atomic force microscopy tips, [72] and PhCs. [59,67,[73][74][75][76][77][78][79][80][81] Briefly, MPP utilizes the nonlinear nature of the multiphoton excitation process to only excite dye molecules in a very small volume around the focal point, with dimensions on the order of the resolution limit.…”
Section: Direct Writingmentioning
confidence: 99%
“…Haske et al reported up to 65 nm thin lines, 6 Juodkazis et al reached 30 nm structures in SU-8 photoresist, 7 and Tan et al even sub-25 nm lines in SCR500. 8 Due to the two-photon absorption and the threshold behavior 9 of the used material, it is possible to reach higher resolution than with the often used laser direct writing process. 10,11 Also the precise control of the processing parameters such as the number of pulses, pulse duration, or pulse energy, for example, allow increasing the resolution.…”
Section: Introductionmentioning
confidence: 99%